The association between prevalent neck pain and health-related quality of life: a cross-sectional analysis - Rezai, Mana (Springer-Verlag, 2008)
The aim of this study was to examine the association between grades of neck pain severity and health-related quality of life (HRQoL), using a population-based, cross-sectional mailed survey. The literature suggests that physical and mental HRQoL is worse for individuals with neck pain compared to those without neck pain. However, the strength of the association varies across studies. Discrepancies in study results may be attributed to the use of different definitions and measures of neck pain and differences in the selection of covariates used as control variables in the analyses. The Saskatchewan Health and Back Pain Survey was mailed to 2,184 randomly selected Saskatchewan adults of whom 1,131 returned the questionnaire. Neck pain was measured with the Chronic Pain Questionnaire and categorized into four increasing grades of severity. We measured HRQoL with the SF-36 Health Survey and computed the physical and mental component summary scores. We built separate multiple linear regression models to examine the association between grades of neck pain and physical and mental summary scores while controlling for sociodemographic, general health and comorbidity covariates. Our crude analysis suggests that a gradient exists between the severity of neck pain and HRQoL. Compared to individuals without neck pain, those with Grades III–IV neck pain have significantly lower physical (mean difference = −13.9/100; 95% CI = −16.4, −11.3) and mental (mean difference = −10.8/100; 95% CI = −13.6, −8.1) HRQoL. Controlling for covariates greatly reduced the strength of association between neck pain and physical HRQoL and accounted for the observed association between neck pain and mental HRQoL. In the comorbidity model, the strength of association between Grades III–IV neck pain and PCS decreased by more than 50% (mean difference = −4.5/100; 95% CI = −6.9, −2.0). In the final PCS model, Grades III–IV neck pain coefficients changed only slightly from the comorbidity model (mean difference = −4.4/100; 95% CI = −6.9, −1.9). This suggests that comorbid conditions account for most of the association between neck pain and PCS score. It was concluded that prevalent neck pain is weakly associated with physical HRQoL, and that it is not associated with mental HRQoL. Our cross-sectional analysis suggests that most of the observed association between prevalent neck pain and HRQoL is attributable to comorbidities.